Meningkatkan Keterampilan menyimak siswa menggunakan metode cerita bergambar pada pelajaran bahasa Indonesia Kelas III SD Negeri 100103 Sitinjak - Sofia Lubis; Nursyaidah Nursyaidah; Ratih Zefira; Djang Nadiya (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This research is motivated by the low listening skills of third grade students of SD Negeri 100103 Sitinjak in Indonesian language lessons on fairy tales because students seem bored with the fairy tales told by the teacher so that students do not listen to the stories being told. In addition, the nonconducive classroom atmosphere makes students more interested in joking with their friends, this causes noise so that students have difficulty concentrating on listening. This study aims to determine whether the picture story method can improve students' listening skills in Indonesian language lessons for third grade students of SD Negeri 100103 Sitinjak. The type of research conducted is Classroom Action Research (PTK). Classroom action research is a study that raises actual problems faced by teachers in the field. Classroom action research is a study that raises actual problems faced by teachers in the field. The research population is all thirdgrade students, totaling 23 students. The data collection technique uses observation and tests. This research was carried out in two cycles in the first cycle, the 1st meeting the number of students who completed was 9 students (39.13%) and those who did not complete as many as 14 students (60.86%), while the first cycle of the 2nd meeting the number of students who completed was 14 students (60.86%) and those who did not complete as many as 9 students (39.13%). In the second cycle of the 1st meeting, the number of students who completed was 17 students (73.91%) and those who did not complete as many as 6 students (26.08%) while in the second cycle of the 2nd meeting there were 20 students (86.95%) and those who did not complete as many as 3 students (13.04%). The results of the study showed that there was an improvement in students' listening skills by using the gamar story method in third grade students of SD Negeri 100103 Sitinjak.